Targeted alpha therapy for glioblastoma - Kunikowska, Jolanta; Morgenstern, Alfred; Pełka, Kacper; Bruchertseifer, Frank; Królicki, Leszek (Frontiers in Medicine, 2022)
According to the 2021 World Health Organization Classification of Tumors of the Central Nervous System, glioblastoma (GB) is a primary brain tumor and presents with the worst prognosis. Due to its infiltrating characteristic, molecular heterogeneity, and only partly preserved function of the blood-brain barrier, the median overall survival time is short (9–15 months), regardless of comprehensive treatment including surgery, radiotherapy, and chemotherapy. Several novel treatment strategies are under investigation. Unfortunately, none of them produced successful results; 90% of patients have a recurrence of the disease within 6 months. Local administration of the drug could be a promising approach to delivering treatment with minimized side effects, due to the recurrence of 95% glioblastomas in a margin of 2 cm at the primary site. Several ligand-receptor systems have been evaluated, such as targeting tenascin, the extracellular matrix protein, or radiolabeled somatostatin analogs, as it is overexpressed with the SSTR-2 receptor system in around 80% of gliomas. Moreover, this study revealed that the NK-1 receptor is overexpressed in GB, suggesting that substance P (SP) may serve as a ligand. A variety of radioisotopes, beta- (131I, 90Y, or 177 Lu) and alpha emitters (213Bi, 225Ac, or 211At), with different physical properties were tested for treatment. Alpha particles have many advantages over beta radiation such as short range with higher linear energy transfer. According to that characteristic, it is extremely dose delivered to the targeted cells, while reducing harm to nearby healthy tissue. Additionally, the biological effect of alpha radiation is independent of the cell cycle phase, cell oxygenation and O-6-methylguanine-DNA methyltransferase (MGMT) gene promoter methylation status. In this article, we summarize the experience with local treatment of primary and secondary GBs with locally used radioisotopes such as [213Bi]Bi-DOTA-SP or [225Ac]Ac-DOTA-SP.